Further use of molecular data in studying biogeographic patterns within the centipede genus Craterostigmus: the case for a monophyletic New Zealand species - Giribet, Gonzalo; Cuéllar, Alejandra Guzmán; Edgecombe, Gregory D. (Soil Organisms, 2009)
A second species of the previously monotypic centipede genus Craterostigmus was recently established on the basis of New Zealand collections (C. crabilli) differing from the Tasmanian C. tasmanianius with respect to diagnostic characters in nuclear 18S and 28S rRNA, coupled with differences in body size, leg spinulation and internal anatomy. Analyses of molecular data resolved the New Zealand species as non-monophyletic because of the isolated phylogenetic position of a population from Lewis Pass on the South Island that had especially divergent cytochrome c oxidase subunit I (COI) sequences. Herein, previously missing 16S rRNA sequences for the Lewis Pass samples are added to the four-gene sample, together with newly collected specimens from South Island and Stewart Island. The more complete dataset retrieves both C. crabilli and C. tasmanianus as monophyletic, and the four-gene analysis dataset shows that Stewart Island and North Island populations fall outside a clade that unites most South Island samples. Despite its favoured role in DNA barcoding, COI performs more poorly than 18S, 28S or 16S rRNAs for identifying species of Craterostigmus.
Keywords: Craterostigmus crabilli; Craterostigmomorpha; COI; 16S rRNA; Lewis Pass; Stewart Island